Efek Penyangga Modal Terhadap Transmisi Kebijakan Moneter Pada Kredit Perbankan Indonesia - Baharuddin, Baharuddin; Fungky Muchsidin, Feronica; A.We Tenri Fatimah Singkeruang; Nuraeni Saeni (Movere Journal, 2026)
This study aims to analyse the determinants and dynamics of Indonesian bank credit growth after the pandemic, focusing on monetary-policy transmission and the moderating role of capital buffer. Using an explanatory quantitative approach, quarterly panel data of 47 commercial banks (Q12020 – Q22025) were estimated with two-step System Generalized Method of Moments (System-GMM). Results show that credit growth exhibits negative dynamic persistence, capital buffer has a significant positive effect, while profitability and macroeconomic variables are insignificant. The central finding is a significantly negative interaction between capital buffer and the BI Rate, validating a capital-hoarding mechanism: well-capitalised banks restrain credit expansion when the policy rate rises. The results are robust to alternative specifications and instrument-validity tests. The study contributes a “Conditional Bank Lending” framework and recommends a dual-speed monetary transmission approach and a more responsive countercyclical capital buffer.